Job satisfaction of primary health care providers: experience from an institution in Lima, Peru - Ramirez, Carlos A. (2014)
Primary care in Peru is understood as medical attention given at precarious healthcare establishments where physicians may not always be present. This phenomenon creates an overflow of patients at specialized healthcare centers with diseases that could very well be treated by a general physician. As a consequence of this transition, physicians and other healthcare professionals who do provide primary care may experience low job satisfaction which could, at the same time, have a negative impact on patient satisfaction.